Which Matters More in Fighting COVID-19—Government Policy or Community Participation? - Qian, Ying; Huang, Jiaoling; Zhao, Laijun; Cheong, Io Hong; Cao, Siqi; Xiong, Li; Zhu, Qin (Frontiers in Public Health, 2022)
Objective: As a heavily populated megacity, Shanghai faces major epidemic risks. However, Shanghai’s control of COVID-19 has been successful owing to both the strict government policy and wide community participation. Here, we investigated the impact of these stakeholders and examined who played a major role across different epidemic stages. Design: We extended the classic SEIR model considering the heterogeneous contact structure in four social sceneries, school, workplace, public entertainment venues and neighbourhood community, which could reflect the impact of lockdown policy and wide participation of residents happened at community level. Result: The simulation results showed that if without lockdown policy and only with community participation, the daily new confirmed cases would gradually increase to more than 7,000 [292/1,000,000] at the end of Sep. However, if without community participation and only with lockdown policy, the daily new confirmed sharply decreased to 30 [1.2/1,000,000] at the end of the first month and remained low for several months. But when lockdown policy was gradually lifted, the new confirmed cases increased exponentially, eventually reaching more than 17,000 [708/1,000,000]. Therefore, government lockdown policy was necessary for the rapid control of COVID-19 during the outbreak stage while community participation is more important in keeping the number of new confirmed cases low during the reopening stage. Conclusion: Government lockdown policy and community participation plays different role in the control of COVID-19 at different stages of the epidemic: although the government played a leading role in setting up policies, the broader participation of community fever clinics and the general public were especially crucial in winning the battle against COVID-19 in the long run.